Islamic bioethics of ordinary and extraordinary means of medical treatment - Malik, Mohammad Manzoor (2014)
The researcher attempted to show the importance of medical treatment from the primary sources of Islam: the Quran and the Sunnah, and, furthermore, how this issue is debated by Muslim jurists in the classics of Islamic jurisprudence. Connecting the traditional discourse to the latest development in Islamic jurisprudence, the researcher showed that medical treatment becomes obligatory (wajib) if its abandonment leads to the fatality of the life or an organ or its inability or the disease transmits to others such as communicable diseases. Deriving on this concept of obligation, the researcher discussed the distinction of ordinary and extraordinary means of medical treatment. The researcher showed that the distinction can be made in two ways regarding terminally ill patients and non- terminally ill patients. The factors that lead to the distinction between ordinary and extraordinary treatment are: (1) patient capacity (2) expert advice, and (3) nature of medication. Regarding terminally ill patients, medical treatment can become extraordinary if it is (1) extraordinary because of patient capacity and (2) extraordinary because of nature of medication. In both these case the condition applies and that is expert advice taken from a group of physicians. In regards to non-terminally ill patients, the three types of extraordinary means of medical treatment are very prominent: (1) treatment that is known to be useless and futile, (2) treatment that may endanger the life or cause more harm than what it removes, and (3) treatment is useful, but the patient is unable to bear the cost.